WOGONIN ON THE MECHANISM OF INFLUENZA VIRUS INFECTION OF ALVEOLAR MACROPHAGE INFLAMMATORY SUBSTANCES - Niyozov, Qahramon Adashaliyevich; Mirzaolimov , Mirzohid Mirzavalievich; Kabirova , Zarnigor Akmaljon qizi (Educational Research in Universal Sciences, 2023)
Influenza caused by influenza virus infection is a highly contagious re spiratory disease. It spreads rapidly and leads to a high mortality rate. R ecently it often happened severe global influenza pandemic, and threatened the public health seriously.